2014
DOI: 10.3389/fnhum.2014.00561
|View full text |Cite
|
Sign up to set email alerts
|

Face processing improvements in prosopagnosia: successes and failures over the last 50 years

Abstract: Clinicians and researchers have widely believed that face processing cannot be improved in prosopagnosia. Though more than a dozen reported studies have attempted to enhance face processing in prosopagnosics over the last 50 years, evidence for effective treatment approaches has only begun to emerge. Here, we review the current literature on spontaneous recovery in acquired prosopagnosia (AP), as well as treatment attempts in acquired and developmental prosopagnosia (DP), differentiating between compensatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 80 publications
(129 reference statements)
1
59
1
1
Order By: Relevance
“…Both literature reviews concluded that restorative training has not yet proven to be very successful and that compensatory strategies appeared to be a more effective approach for the rehabilitation of acquired prosopagnosia (Bate & Bennetts, 2014;DeGutis, Chiu, Grosso, & Cohan, 2014). The additional eight articles appeared to be in line with the outcome of the literature reviews, especially with regard to transferring the training to real-life face recognition (Bate et al, 2015).…”
Section: Prosopagnosia and Object Agnosiasupporting
confidence: 58%
“…Both literature reviews concluded that restorative training has not yet proven to be very successful and that compensatory strategies appeared to be a more effective approach for the rehabilitation of acquired prosopagnosia (Bate & Bennetts, 2014;DeGutis, Chiu, Grosso, & Cohan, 2014). The additional eight articles appeared to be in line with the outcome of the literature reviews, especially with regard to transferring the training to real-life face recognition (Bate et al, 2015).…”
Section: Prosopagnosia and Object Agnosiasupporting
confidence: 58%
“…Why doesn't the intact hemisphere come to mediate recognition, especially if, as we have claimed, the representations in the non‐preferred hemisphere play a functional role and are not merely epiphenomenal? The existing evidence, however, suggests otherwise, and to date, there is rather little reported recovery of function in pure alexia or in acquired forms of prosopagnosia …”
Section: Implications For Recoverymentioning
confidence: 97%
“…Given the rarity of acquired prosopagnosia, it will be very difficult to establish the impact of each of these factors. To date, there have been few remedial attempts for the acquired variant, and most focus on enhancing coping strategies to circumvent poor face recognition 158,159. Only one published study attempted to improve face recognition, in a child with diffuse damage after meningococcal meningitis: 18 months of training did not improve matters 160.…”
Section: Treatment and Rehabilitationmentioning
confidence: 99%